More milk, meat and eggs for growing and nourishing Rwanda's next generation - International Livestock Research Institute (International Livestock Research Institute, 2021)
In Rwanda, chronic malnutrition amongst small children remains high. Through a USAID Feed the Future Innovation Lab for Livestock Systems funded project, ILRI and partners conducted a social behavior change communication campaign to encourage families to consume more animal source foods. Messages that are being delivered by community health workers are directed at pregnant and lactating mothers and young children, who are most susceptible to malnutrition.